Pengembangan Dan Validasi Kueisoner Untuk Mengukur Kepuasan Pasien Terhadap Penerapan Telefarmasi Di Apotek - Martania Pratiwi; Umatul Khoiriyah; Suci Hanifah (LPPM Universitas Abdurrab, 2023)
Customer satisfaction surveys measure how satisfied consumers are with relevant product or service attributes and the importance of those attributes. In general, surveys use a five-point scale (Schiffman et al., 2010). Patient satisfaction can be revealed through several measuring tools. Questionnaires or assessment instruments are tools used to apply all content validity methods. The final result of content validity is an assessment of the appropriateness of the test content. Lawshe proposed a method called the content validity ratio as a result of measuring expert assessments of their agreement on content validity using statistical techniques of agreement between raters. The process of reviewing items by a panel of experts by providing input from validators is used as a reference to compose sentences that are more appropriate to the aspects and easy to understand. So to get a patient satisfaction questionnaire regarding the implementation of telepharmacy in pharmacies, some validation evidence is needed which can then produce a proper, valid questionnaire. and reliable for use in analysis of pharmacy telepharmacy patient satisfaction. To collect evidence of the validity of knowing and obtaining an instrument (questionnaire) that can be used to measure patient satisfaction with the implementation of telepharmacy services in pharmacies. Expert review (dianalisis CVI), Proses respon, Evaluasi struktur : internal struktur dengan EFA (eksplratory factor analysis) dan reliabilitas. From the SPSS results, analysis of factor loading values ​​with Cronbach's alpha shows that the total reliability score for the expected attribute is 0.977 for factor 1, expected 0.973 and 0.926 for factor 2, expected 0.926. Meanwhile, the results of the reality reliability test, the total Cronbach's alpha score, was 0.979, with the Cronbach's alpha value for factor 1 being 0.976 and factor 2 being 0.931. From the reliability data used for each subscale it is above 0.9 so that the question statement items with Cronbach's alpha values ​​are below 0.9 will experience elimination. A total of 10 questions were eliminated because the reliability value was below 0.9. The higher the Cronbach' alpha value, the more valid, good and reliable an item is said to be. The patient satisfaction questionnaire has sufficient evidence of validity including evidence of content validity, response process and internal structure.